Stable lithium / sodium ion battery electrolyte and battery thereof

By adding stabilizers to the electrolyte to inhibit the formation and decomposition of fluorinated polymers, the problem of battery performance degradation caused by discoloration of the electrolyte is solved, and the battery's excellent performance in high and low temperature environments is achieved.

CN119340476AActive Publication Date: 2025-01-21ZHEJIANG LANTIAN ENVIRONMENTAL PROTECTION HI TECH CO LTD +2
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202310883892.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-19
Publication Date
2025-01-21
Estimated Expiration
2043-07-19

AI Technical Summary

Technical Problem

The electrolyte containing the boron trifluoride composite metal salt of pyrosulfate is prone to discoloration during storage, resulting in deterioration of the electrochemical performance of the battery, especially in high and low temperature environments.

Method used

An electrolyte containing boron trifluoride composite metal salt of pyrosulfate and a stabilizer is used. The stabilizer prevents discoloration of the electrolyte and enhances the cycle performance of the battery by inhibiting the fluorination of the -B-F group and neutralizing the Lewis acid. and high and low temperature performance.

Benefits of technology

Improve the stability of the electrolyte, prevent discoloration, and significantly improve the circulating performance, high temperature storage performance and low temperature performance of lithium ion/sodium ion battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340476A_ABST
    Figure CN119340476A_ABST
Patent Text Reader

Abstract

The invention discloses a stable lithium / sodium ion battery electrolyte and a battery thereof, the electrolyte comprises a main lithium salt, a non-aqueous solvent and an additive, the additive comprises: a first additive, the first additive at least comprises a novel composite metal salt having a structure represented by the following formula (I-1), and the use amount of the first additive accounts for 0.01-15.0 wt% of the total mass of the electrolyte: # imgabs0 # M is Li or Na; and the second additive is a stabilizer, and the dosage of the second additive accounts for 0.001-1.0 wt% of the total mass of the electrolyte. The second additive can improve the stability of the first additive, not only inhibits the generation of a fluorinated polymer in the first additive, but also inhibits the decomposition of-S-O-B-groups in the first additive, enhances the performance of the additive, and further improves the cycle performance and high and low temperature performance of the battery under high voltage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrolytes, and in particular to an electrolyte comprising a pyrosulfate boron trifluoride composite metal salt and a stabilizer, and application of the electrolyte in a lithium ion battery or a sodium ion battery. Background Art

[0002] As an indispensable component of lithium-ion / sodium-ion batteries, electrolyte additives are mainly responsible for constructing a stable electrode / electrolyte interface film to achieve electronic insulation and facilitate the transmission of lithium ions / sodium ions. Under the influence of different functional groups in the additives, the composition and structure of the battery interface film change, ultimately affecting the battery's cycle life, high-temperature storage, and low-temperature discharge performance.

[0003] As the requirements for battery volume energy density become higher and higher, increasing the battery operating voltage and developing high-voltage electrolytes are the current mainstream methods, but high voltage will cause the various electrochemical properties of the battery to decay, which puts higher requirements on the performance of electrolyte additives. Furthermore, in order to simultaneously meet the working performance of the battery in high-temperature and low-temperature environments, the electrolyte is required to have both excellent high-temperature and low-temperature performance. At present, most electrolyte additives only have high-temperature performance or low-temperature performance unilaterally, and a combination of high-temperature additives and low-temperature additives is required to simultaneously meet the high and low-temperature performance of the battery.

[0004] Pyrosulfate boron trifluoride composite lithium salt is a new type of electrolyte additive with both high and low temperature performance developed by Zhejiang Chemical Research Institute Co., Ltd. Its patent CN202211583064.X discloses that the additive can simultaneously improve the battery's cycle performance, high temperature storage performance and low temperature performance. At the same time, patent CN202211583043.8 also discloses the use of pyrosulfate boron trifluoride composite lithium salt, vinyl sulfate and / or 1,3-propane sultone in combination, or further adding vinylene carbonate in combination, so that lithium-ion batteries still have excellent cycle performance, high temperature storage performance and the effect of inhibiting battery gas production in high energy density systems and high voltage environments, and can also inhibit the impedance growth during the battery cycle and further improve the low temperature performance.

[0005] Therefore, it is also an important research topic to continue in-depth research to develop more stable, safe and environmentally friendly pyrosulfate boron trifluoride complex metal salt compositions and electrolyte formulas to meet the battery performance requirements in high energy density systems and high voltage scenarios. Summary of the invention

[0006] The present invention has found in the further research process that as the storage time of the electrolyte increases, the chromaticity of the electrolyte containing the pyrosulfate boron trifluoride composite metal salt increases, and even presents a reddish brown color. It is speculated through research that the sulfate group and sulfonic acid group in the pyrosulfate boron trifluoride composite metal salt will aggravate the acidity of the electrolyte under the action of the electron-deficient boron component, thereby causing the polymerization reaction of solvent molecules such as ethylene carbonate (EC) and ethyl methyl carbonate (EMC) to produce polymers containing conjugated double bonds, and the discoloration of the electrolyte is aggravated; at the same time, the chromaticity problem caused by the side reaction of the electrolyte is also accompanied by the deterioration of the electrochemical performance of the battery, and the battery cycle performance and high-temperature storage performance are significantly reduced.

[0007] In order to solve the above technical problems, the present invention further proposes an electrolyte comprising a pyrosulfate boron trifluoride composite metal salt and a stabilizer and its application in lithium ion / sodium ion batteries. During use, the electrolyte not only enables the lithium ion / sodium ion battery to have high-temperature cycle performance, high-temperature storage performance and low-temperature performance under high voltage, but also improves the stability of the electrolyte, inhibits the discoloration of the electrolyte, and solves the problem of degradation of the battery electrochemical performance caused by chromaticity problems caused by decomposition of the electrolyte.

[0008] The objective of the present invention is achieved through the following technical solutions:

[0009] A stable lithium / sodium ion battery electrolyte comprises a main salt, a non-aqueous solvent and an additive, wherein the additive comprises:

[0010] The first additive comprises at least a novel composite metal salt having a structure shown in the following formula (I-1), and the amount thereof accounts for 0.01 to 15.0 wt% of the total mass of the electrolyte:

[0011]

[0012] In formula (I-1), M is Li or Na; preferably, M is Li;

[0013] The second additive is a stabilizer, selected from at least one of the compounds shown in the following structures, and the amount used is 0.001 to 1.0 wt% of the total mass of the electrolyte:

[0014]

[0015] During the preparation process of the first additive of the present invention, due to different preparation processes, in addition to the novel composite metal salt having the structure shown in the above-mentioned (I-1), at least one of the compounds shown in the following formulas (I-2), (I-3), (I-4), (I-5), and (I-6) is included:

[0016]

[0017]

[0018] In formula (I-2), (I-3), (I-4), (I-5), (I-6), M is Li or Na;

[0019] The first additive contains at least 80 wt % or more of the novel composite lithium salt having the structure shown in formula (I-1). Preferably, the first additive contains 80-95 wt % of the novel composite lithium salt having the structure shown in formula (I-1), and the rest is at least one of compounds (I-2), (I-3), (I-4), (I-5) or (I-6).

[0020] Preferably, the amount of the first additive is 0.2-5.0 wt % of the total mass of the electrolyte, more preferably 0.5-2 wt %.

[0021] The amount of the second additive is 0.001-1.0 wt % of the total mass of the electrolyte, more preferably 0.01-0.1 wt %, and even more preferably 0.02-0.05 wt %.

[0022] Furthermore, the second additive is at least one selected from compounds (II-1), (II-2), (II-3), and (II-8).

[0023] The -SOB- group in the first additive of the present invention can form a cross-linked network interface film containing S and B at the electrode interface during the charge and discharge process of the battery, thereby regulating the M 2 SO 4 、M 2 SO 3 、M 2 SO 4 、M 2 SO 3 (M is Li or Na) and other inorganic salt content, effectively reducing the internal resistance of the battery and improving the low temperature performance of the battery. At the same time, the cross-linked network interface film contains more Li-conducting + Or Na + The pores of the first additive are large, the ionic conductivity is high, and the low-temperature performance of the battery is significantly improved. However, when the first additive exists alone, its -SOB- group is easily decomposed, resulting in the weakening of its advantageous performance effect in the battery electrolyte. In addition, the -BF group in the first additive has a strong fluorination effect and is easy to react with organic solvents to form fluorinated polymers, causing the electrolyte to change color.

[0024] The second additive structure of the present invention contains reducing and weakly basic groups, which can not only inhibit the 6 or NaPF 6 Decomposition and neutralization of PF 5 or POF3 Lewis acids such as -BF can also combine with the -BF group in the first additive, weaken the fluorination of the -BF group, inhibit the formation of fluorinated polymers, and improve the stability of the electrolyte. At the same time, not only does the second additive itself have the ability to annihilate the oxidizing components produced by the positive electrode, which can improve the electrochemical performance of the battery at high voltage and high temperature, but the second additive can also inhibit the decomposition of the -SOB- group in the first additive, strengthen the performance advantages of the first additive, and further improve the battery cycle performance and high and low temperature performance.

[0025] According to the above stable lithium / sodium ion battery electrolyte, the main salt is a main lithium salt or a main sodium salt.

[0026] The main lithium salt is selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium perchlorate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium bis(fluorosulfonylimide), lithium bis(trifluoromethylsulfonylimide), lithium tetrafluorooxalatephosphate, lithium trioxalatephosphate or lithium difluorobis(oxalatophosphate);

[0027] The main sodium salt is selected from at least one of sodium hexafluorophosphate, sodium tetrafluoroborate, sodium hexafluoroarsenate, sodium perchlorate, sodium bisoxalatoborate, sodium difluorooxalatoborate, sodium bis(fluorosulfonyl)imide, sodium bis(trifluoromethylsulfonyl)imide, sodium tetrafluorooxalatophosphate, sodium trioxalatophosphate or sodium difluorobis(oxalatophosphate).

[0028] The non-aqueous solvent is selected from at least one of C3-C6 carbonate or fluorinated carbonate compounds, C3-C8 carboxylic acid ester or fluorinated carboxylic acid ester compounds, sulfone compounds or ether compounds;

[0029] Preferably, the C3-C6 carbonate or fluorocarbonate compound is selected from at least one of ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, dipropyl carbonate, methyl propyl carbonate or ethyl propyl carbonate; the C3-C8 carboxylic acid ester or fluorocarboxylic acid ester compound is selected from at least one of γ-butyrolactone, methyl acetate, methyl propionate, methyl butyrate, ethyl acetate, ethyl propionate, ethyl butyrate, propyl acetate and propyl propionate; the sulfone compound is selected from at least one of cyclopentane sulfoxide, dimethyl sulfoxide, dimethyl sulfone or diethyl sulfone; the ether compound is selected from at least one of triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, ethylene glycol dimethyl ether and dioxolane.

[0030] Generally, the non-aqueous solvent in the lithium ion battery electrolyte and the sodium ion battery electrolyte can be the same. Therefore, the above non-aqueous solvent can be applied to the lithium ion battery electrolyte or the sodium ion battery electrolyte.

[0031] The additives also include basic additives, which are selected from at least one of fluoroethylene carbonate, vinylene carbonate, tris(trimethylsilyl) phosphate, 1,3-propylene sultone, lithium difluorophosphate, lithium bis(fluorosulfonyl)imide, succinic anhydride, adiponitrile, cyclohexylbenzene, lithium difluorobis(oxalate)phosphate, lithium difluorooxalatoborate, sodium difluorooxalatoborate, sodium difluorophosphate, sodium bis(fluorosulfonyl)imide or sodium difluorobis(oxalate)phosphate, and any one of the basic additives accounts for 0.1 to 5 wt% of the total mass of the electrolyte, and the basic additive is different from the main salt, and is used to meet the application scenarios of different electrolytes and the electrochemical performance requirements of the battery.

[0032] In a specific embodiment, a highly stable lithium-ion battery electrolyte is provided, comprising a main salt, a non-aqueous solvent, a first additive, a second additive and a basic additive, wherein the main salt is preferably LiPF 6 , the molar concentration in the non-aqueous solvent is 0.5-2.0 mol / L; the non-aqueous solvent is preferably at least one of ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC), and more preferably a mixed solvent of EC, EMC and DEC, and the mass ratio of the three is EC:EMC:DEC=4:4:2, 3:4:3, 3:5:2 or 3:3:4, etc. The first additive and the second additive are as described above, and the first additive is a composite lithium salt; the basic additive includes: vinylene carbonate, fluoroethylene carbonate, 1,3-propylene sultone, lithium difluorophosphate and lithium difluorooxalate borate, and the amount accounts for 0.5-2wt% of the total mass of the electrolyte.

[0033] In another specific embodiment, a highly stable sodium ion battery electrolyte is provided, comprising a main salt, a non-aqueous solvent, a first additive, a second additive and a base additive, wherein the main salt is preferably NaPF 6 , the molar concentration in the non-aqueous solvent is 0.5-2.0 mol / L; the non-aqueous solvent is preferably at least one of ethylene carbonate (EC), ethyl methyl carbonate (EMC), and propylene carbonate (PC), and is more preferably a mixed solvent of EC, EMC, and PC, and the mass ratio of the three is EC:EMC:PC=7:10:1, 3:4:3, 3:5:2 or 4:4:2, etc.; the first additive and the second additive are as described above, and the first additive is a composite sodium salt; the basic additive includes: vinylene carbonate, 1,3-propylene sultone, sodium difluorooxalatoborate, sodium bis(fluorosulfonyl)imide and sodium bis(oxalatodifluorophosphate), and the amount accounts for 0.5-2wt% of the total mass of the electrolyte.

[0034] The present invention provides a lithium ion secondary battery, comprising a positive electrode, a negative electrode and a separator, wherein the lithium ion secondary battery is filled with any of the above-mentioned electrolytes.

[0035] Specifically, the active material of the positive electrode is selected from nickel-cobalt-manganese ternary materials, nickel-cobalt-aluminum ternary materials, lithium cobaltate materials or lithium iron phosphate materials, and the active material of the negative electrode is selected from graphite, silicon carbide, silicon monoxide, silicon, tin, metallic lithium or their composite materials.

[0036] The present invention also provides a sodium ion secondary battery, including a positive electrode, a negative electrode and a separator, and the electrolyte as described in any one of the above is filled in the sodium ion secondary battery.

[0037] The active material of the positive electrode sheet is selected from NaMn (1-x-y) Ni y M x O 2 (0 ≤ x, y ≤ 1, M is Cu, Fe, Co), sodium manganate, sodium vanadium phosphate, sodium fluorovanadate, sodium iron phosphate, sodium manganese phosphate, Na x MnFe(CN) 6 (0 < x ≤ 2) and at least one of them, and the active material of the negative electrode sheet is selected from hard carbon, carbon black, amorphous carbon, graphite, SnS 2 、Na 2 Ti 3 O 7 、silicon-based materials, metal oxides, metal sulfides or metallic sodium and at least one of them.

[0038] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0039] Through the synergistic effect of the first additive and the second additive of the present invention, the second additive can significantly improve the stability of the first additive and improve the electrochemical performance of the battery at high voltage and high temperature. Specifically, in the first aspect, the second additive can inhibit the formation of fluorinated polymers of the first additive and inhibit the discoloration of the electrolyte; in the second aspect, the second additive can inhibit the decomposition of the -S-O-B- group in the first additive and strengthen the advantageous performance of the first additive, further improving the cycle performance and high and low temperature performance of the battery; in the third aspect, the second additive itself has the ability to annihilate the oxidizing components generated by the positive electrode, which helps to improve the electrochemical performance of the battery at high voltage and high temperature. Specific embodiments

[0040] The present invention will be further described below in conjunction with specific embodiments, but the present invention is not limited to these specific embodiments. Those skilled in the art should recognize that the present invention covers all alternative solutions, improvement solutions and equivalent solutions that may be included within the scope of the claims.

[0041] In the embodiments and comparative examples of the present invention, the types of the first additive include the following several:

[0042] The first additive A contains 95 wt% of compound I-1 and 5 wt% of compound I-2, both of which are composite lithium salts;

[0043] The first additive B contains 90 wt% of compound I-1, 6 wt% of compound I-2 and 4 wt% of compound I-3, and all of them are composite lithium salts;

[0044] The first additive C contains 85 wt % of compound I-1, 7 wt % of compound I-2, 5 wt % of compound I-3 and 3 wt % of compound I-4, and all of them are composite lithium salts.

[0045] The first additive D contains 95 wt % of compound I-1 and 5 wt % of compound I-2, and both are complex sodium salts.

[0046] 1. Preparation of electrolyte

[0047] Preparation of basic electrolyte 1: In a glove box filled with argon (water content <5ppm, oxygen content <10ppm), ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) were uniformly mixed at a mass ratio of EC:EMC:DEC=4:4:2, and then lithium hexafluorophosphate (LiPF6) was slowly added to the mixed solution. 6 ) to a molar concentration of 1.0 mol / L to obtain basic electrolyte 1.

[0048] Preparation of basic electrolyte 2: In a glove box filled with argon (water content <5ppm, oxygen content <10ppm), propylene carbonate (PC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) were uniformly mixed at a mass ratio of EC:EMC:PC=7:10:1, and sodium hexafluorophosphate (NaPF 6 ) to NaPF 6 The molar concentration is 1.0 mol / L, and basic electrolyte 2 is obtained.

[0049] Example 1

[0050] 0.5 wt % of the first additive A and 0.01 wt % of the compound II-1 were added to the basic electrolyte 1 to obtain the electrolyte of this example.

[0051] Example 2

[0052] 0.5 wt % of the first additive A and 0.05 wt % of the compound II-1 were added to the basic electrolyte 1 to obtain the electrolyte of this example.

[0053] Example 3

[0054] 1.0 wt % of the first additive A and 0.1 wt % of the compound II-1 were added to the basic electrolyte 1 to obtain the electrolyte of this example.

[0055] Example 4

[0056] 2 wt % of the first additive A and 0.1 wt % of the compound II-1 were added to the basic electrolyte 1 to obtain the electrolyte of this example.

[0057] Example 5

[0058] 5 wt % of the first additive A and 0.1 wt % of the compound II-1 were added to the basic electrolyte 1 to obtain the electrolyte of this example.

[0059] Example 6

[0060] 15 wt % of the first additive A and 1.0 wt % of the compound II-1 were added to the basic electrolyte 1 to obtain the electrolyte of this example.

[0061] Example 7

[0062] 0.01 wt % of the first additive A and 0.02 wt % of the compound II-6 were added to the basic electrolyte 1 to obtain the electrolyte of this example.

[0063] Example 8

[0064] 0.5 wt % of the first additive A and 0.2 wt % of the compound II-1 were added to the basic electrolyte 1 to obtain the electrolyte of this example.

[0065] Example 9

[0066] 0.5 wt % of the first additive A and 0.001 wt % of the compound II-6 were added to the basic electrolyte 1 to obtain the electrolyte of this example.

[0067] Example 10

[0068] 0.5 wt % of the first additive A and 0.02 wt % of the compound II-2 were added to the basic electrolyte 1 to obtain the electrolyte of this example.

[0069] Embodiment 11

[0070] 0.5 wt % of the first additive B and 0.02 wt % of the compound II-3 were added to the basic electrolyte 1 to obtain the electrolyte of this example.

[0071] Example 12

[0072] 1 wt % of the first additive B and 0.03 wt % of the compound II-4 were added to the basic electrolyte 1 to obtain the electrolyte of this example.

[0073] Example 13

[0074] 0.5 wt % of the first additive C and 0.05 wt % of the compound II-5 were added to the basic electrolyte 1 to obtain the electrolyte of this example.

[0075] Embodiment 14

[0076] 1.0 wt % of the first additive C and 0.05 wt % of the compound II-7 were added to the basic electrolyte 1 to obtain the electrolyte of this example.

[0077] Embodiment 15

[0078] In the basic electrolyte 1, 0.5 wt% of the first additive A, 0.05 wt% of the compound II-1 and 1.0 wt% of VC were added to obtain the electrolyte of this example.

[0079] Example 16

[0080] In the basic electrolyte 1, 0.5 wt% of the first additive A, 0.05 wt% of the compound II-1 and 1.0 wt% of FEC were added to obtain the electrolyte of this example.

[0081] Embodiment 17

[0082] In the basic electrolyte 1, 0.5 wt% of the first additive A, 0.02 wt% of the compound II-2, 1.0 wt% of VC and 1.0 wt% of LiPO were added. 2 F 2 , and obtain the electrolyte of this embodiment.

[0083] Embodiment 18

[0084] 0.5 wt % of the first additive D and 0.05 wt % of the compound II-3 were added to the basic electrolyte 2 to obtain the electrolyte of this example.

[0085] Embodiment 19

[0086] In the basic electrolyte 2, 1 wt% of the first additive D and 0.05 wt% of the compound II-8 were added to obtain the electrolyte of this example.

[0087] Embodiment 20

[0088] In the basic electrolyte 2, 1 wt% of the first additive D, 0.05 wt% of the compound II-8 and 1 wt% of PS were added to obtain the electrolyte of this example.

[0089] Comparative Example 1

[0090] 0.5 wt % of the first additive A was added to the basic electrolyte 1 to obtain the electrolyte of this comparative example.

[0091] Comparative Example 2

[0092] 0.5 wt % of the first additive B was added to the basic electrolyte 1 to obtain the electrolyte of this comparative example.

[0093] Comparative Example 3

[0094] 0.05 wt % of compound II-1 was added to the basic electrolyte 1 to obtain the electrolyte of this comparative example.

[0095] Comparative Example 4

[0096] 1 wt % of the first additive A and 1.5 wt % of the compound II-1 were added to the basic electrolyte 1 to obtain the electrolyte of this comparative example.

[0097] Comparative Example 5

[0098] 1 wt % of the first additive A and 0.0001 wt % of the compound II-1 were added to the basic electrolyte 1 to obtain the electrolyte of this comparative example.

[0099] Comparative Example 6

[0100] 1 wt % of the first additive A and 0.1 wt % of pyridine were added to the basic electrolyte 1 to obtain the electrolyte of this comparative example.

[0101] Comparative Example 7

[0102] Basic electrolyte 1 was used as the electrolyte in this comparative example.

[0103] Comparative Example 8

[0104] 1 wt % of the first additive D was added to the basic electrolyte 2 to obtain the electrolyte of this comparative example.

[0105] Comparative Example 9

[0106] 0.05 wt % of compound II-8 was added to the basic electrolyte 2 to obtain the electrolyte of this comparative example.

[0107] Comparative Example 10

[0108] Basic electrolyte 2 was used as the electrolyte in this comparative example.

[0109] 2. Electrolyte storage chromaticity test

[0110] A portion of the prepared electrolyte of the embodiment and the comparative example was transferred into a sealed aluminum bottle and stored in a constant temperature oven at 50°C. The chromaticity value of the electrolyte was tested in a glove box before storage, after 7 days of storage, and after 28 days of storage. The chromaticity test method adopted the platinum-cobalt colorimetry method, and the chromaticity unit was Hazen. The test results are shown in Table 1 below:

[0111] Table 1 Electrolyte chromaticity test results

[0112]

[0113]

[0114] It can be seen from Table 1 above that the use of the first additive will lead to a decrease in the chromaticity stability of the electrolyte, while the second additive has a significant effect of reducing the chromaticity of the electrolyte.

[0115] Comparing Example 3, Example 4 and Example 5, it can be seen that the chromaticity of the electrolyte increases with the increase in the amount of the first additive A. Comparing Example 1, Example 2 and Example 8, it can be seen that the increase in the content of Compound II-1 can further reduce the chromaticity of the electrolyte.

[0116] 3. Electrochemical performance test

[0117] The electrolytes of Examples 1 to 17 and Comparative Examples 1 to 7 are respectively made into soft-pack lithium-ion batteries with a capacity of 1260 mAh. The lithium-ion batteries include a positive electrode sheet, a negative electrode sheet, a separator, an electrolyte and battery auxiliary materials. The positive electrode active material is a ternary positive electrode LiNi 0.6 Co 0.2 Mn 0.2 O 2 The negative electrode active material is high-capacity graphite. The preparation process is as follows: the positive electrode sheet, the separator and the negative electrode sheet are wound together into a roll core, sealed with an aluminum plastic film and then baked to make the electrode moisture meet the requirements, and the battery cell is injected with electrolyte after baking, and the finished lithium-ion battery soft pack battery cell is obtained through the steps of standing, forming, capacity separation and aging.

[0118] The electrolytes of Examples 18 to 20 and Comparative Examples 8 to 10 were respectively made into sodium ion batteries with a soft pack capacity of 1000 mAh. The sodium ion batteries included a positive electrode sheet, a negative electrode sheet, a separator, an electrolyte and battery auxiliary materials. The positive electrode active material was a ternary positive electrode NaNi 0.33 Fe 0.33 Mn 0.33 O 2The negative electrode active material is hard carbon. The preparation process is as follows: the positive electrode sheet, the separator and the negative electrode sheet are wound together into a roll core, sealed with an aluminum plastic film and then baked to make the electrode moisture meet the requirements, and the battery cell is injected with electrolyte after baking, and the finished sodium ion soft-pack battery cell is obtained through the steps of standing, forming, volume separation and aging.

[0119] The performance test (test voltage 2.8-4.2V) of the lithium ion battery and sodium ion battery prepared above mainly includes:

[0120] (1) 60°C high temperature storage test: The battery was charged to 100% SOC and stored in a 60±2°C oven for 28 days. The volume before and after storage was tested to obtain the volume expansion rate of the single battery before and after 60°C storage.

[0121] (2) 45°C high temperature cycle test: The battery is cycled in a 45±1°C oven at a charge and discharge current of 1C / 1C. The discharge capacity per week is calculated. The cycle is stopped after 500 cycles, and the capacity retention rate after the cycle is calculated.

[0122] (3) -20℃ low-temperature discharge: The battery is discharged in a -20±1℃ oven at a discharge current of 1C to 80% of the lower limit voltage. The low-temperature discharge capacity is taken as the percentage of the 1C discharge capacity at 25℃, which is recorded as the low-temperature discharge capacity retention rate.

[0123] The test results are shown in Table 2 below:

[0124] Table 2 Battery electrochemical performance test results

[0125]

[0126]

[0127] As shown in Table 2 above, adding the first additive A, the first additive B or the first additive C to the electrolyte of the lithium-ion battery can reduce the initial impedance of the battery, improve the low-temperature discharge performance, and inhibit the gas production and impedance growth of the battery during high-temperature storage, and improve the cycle performance, so as to achieve the effect of taking into account both high and low temperature performance. At the same time, using the first additive D in the sodium-ion battery can also achieve the same effect.

[0128] It can be seen from Table 2 above that the addition of the second additive can significantly improve the electrochemical performance of the battery. The reason is that the addition of the second additive can inhibit the decomposition of the -SOB- group in the first additive, strengthen the advantageous performance of the first additive, and further improve the cycle performance and high and low temperature performance of the battery.

[0129] By comparing Examples 2 to 6, it can be seen that as the amount of the first additive A increases, the overall battery performance improves first, and as the amount of the first additive A further increases, the battery performance cannot continue to improve, and the optimal amount of addition is about 0.5 to 2.0 wt%.

[0130] By comparing Example 15 with Example 2, it can be found that adding the first additive A, the second additive and VC to the electrolyte at the same time can not only avoid the defect of VC increasing the initial impedance of the battery, but also further improve the high temperature storage performance and cycle performance. By comparing Example 17 with Example 2 and Example 15, it can be found that on the basis of adding the first additive and the second additive, adding VC, LiPO 2 F 2 Conventional additives such as iodine and iodine can further improve the high and low temperature performance of the battery.

Claims

1. A stable lithium / sodium ion battery electrolyte, comprising a main salt, a non-aqueous solvent and an additive, characterized in that: The additives include: The first additive comprises at least a novel composite metal salt having a structure shown in the following formula (I-1), and the amount thereof accounts for 0.01 to 15.0 wt% of the total mass of the electrolyte: In formula (I-1), M is Li or Na; The second additive is a stabilizer, selected from at least one of the compounds shown in the following structures, and the amount used is 0.001 to 1.0 wt% of the total mass of the electrolyte:

2. The stable lithium / sodium ion battery electrolyte according to claim 1, characterized in that: The M is Li.

3. The stable lithium / sodium ion battery electrolyte according to claim 1, characterized in that: The first additive further comprises at least one of the compounds represented by the following formulae (I-2), (I-3), (I-4), (I-5), and (I-6): In formula (I-2), (I-3), (I-4), (I-5), (I-6), M is Li or Na; The first additive contains at least 80 wt % of the novel composite metal salt having the structure represented by formula (I-1).

4. The stable lithium / sodium ion battery electrolyte according to claim 3, characterized in that: The first additive contains 80 to 95 wt % of the novel composite metal salt having the structure represented by the formula (I-1), and the rest is at least one of compounds (I-2), (I-3), (I-4), (I-5) or (I-6).

5. The stable lithium / sodium ion battery electrolyte according to claim 1, characterized in that: The amount of the first additive used accounts for 0.2-5.0 wt % of the total mass of the electrolyte.

6. The stable lithium / sodium ion battery electrolyte according to claim 1, characterized in that: The amount of the second additive is 0.01-0.1 wt % of the total mass of the electrolyte.

7. The stable lithium / sodium ion battery electrolyte according to claim 1, characterized in that: The second additive is at least one selected from compounds (II-1), (II-2), (II-3), and (II-8).

8. The stable lithium / sodium ion battery electrolyte according to claim 1, characterized in that: The main salt is a main lithium salt or a main sodium salt, and the main lithium salt is selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium perchlorate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium bis(fluorosulfonylimide), lithium bis(trifluoromethylsulfonylimide), lithium tetrafluorooxalatephosphate, lithium trioxalatephosphate or lithium difluorobis(oxalatophosphate); the main sodium salt is selected from at least one of sodium hexafluorophosphate, sodium tetrafluoroborate, sodium perchlorate, sodium bis(fluorosulfonylimide), sodium bis(trifluoromethylsulfonylimide) or sodium difluorophosphate.

9. The stable lithium / sodium ion battery electrolyte according to claim 1, characterized in that: The non-aqueous solvent is selected from at least one of C3-C6 carbonate or fluorinated carbonate compounds, C3-C8 carboxylic acid ester or fluorinated carboxylic acid ester compounds, sulfone compounds or ether compounds; The C3-C6 carbonate or fluorocarbonate compound is selected from at least one of ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, dipropyl carbonate, methyl propyl carbonate or ethyl propyl carbonate; the C3-C8 carboxylic acid ester or fluorocarboxylic acid ester compound is selected from at least one of γ-butyrolactone, methyl acetate, methyl propionate, methyl butyrate, ethyl acetate, ethyl propionate, ethyl butyrate, propyl acetate and propyl propionate; the sulfone compound is selected from at least one of cyclopentane sulfoxide, dimethyl sulfoxide, dimethyl sulfone or diethyl sulfone; the ether compound is selected from at least one of triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, ethylene glycol dimethyl ether and dioxolane.

10. The stable lithium / sodium ion battery electrolyte according to any one of claims 1 to 9, characterized in that: The additives also include basic additives, selected from at least one of fluoroethylene carbonate, vinylene carbonate, tris(trimethylsilyl) phosphate, 1,3-propylene sultone, lithium difluorophosphate, lithium bis(fluorosulfonyl)imide, succinic anhydride, adiponitrile, cyclohexylbenzene, lithium difluorobis(oxalate)phosphate, lithium difluorooxalatoborate, sodium difluorooxalatoborate, sodium difluorophosphate, sodium bis(fluorosulfonyl)imide, and sodium difluorobis(oxalate)phosphate, and any one of the basic additives accounts for 0.1 to 5.0 wt% of the total mass of the electrolyte, and the basic additive is different from the main salt.

11. A lithium / sodium ion secondary battery, comprising a positive electrode, a negative electrode and a separator, characterized in that: The lithium / sodium ion secondary battery is filled with the electrolyte according to any one of claims 1-10.

12. The lithium / sodium ion secondary battery according to claim 11, characterized in that: In the lithium-ion secondary battery, the active material of the positive electrode is selected from nickel-cobalt-manganese ternary material, nickel-cobalt-aluminum ternary material, lithium cobalt oxide material or lithium iron phosphate material, and the active material of the negative electrode is selected from graphite, silicon carbon, silicon oxide, silicon, tin, metallic lithium or a composite material thereof; In a sodium-ion secondary battery, the active material of the positive electrode is selected from NaMn (1-x-y) Ni y M x O2 (0 ≤ x, y ≤ 1, M is Cu, Fe, Co), sodium manganate, sodium vanadium phosphate, sodium fluorovanadium phosphate, sodium iron phosphate, sodium manganese phosphate, Na x MnFe(CN)6 (0 < x ≤ 2), and the active material of the negative electrode is selected from at least one of hard carbon, carbon black, amorphous carbon, graphite, SnS2, Na2Ti3O7, silicon-based materials, metal oxides, metal sulfides, or metallic sodium.

Citation Information

Patent Citations

  • High-energy-density battery electrolyte

    CN118173885A

  • Application of pyrosulfate boron trifluoride composite lithium salt in electrolyte

    CN118173890A

  • Non-aqueous electrolyte of high-voltage lithium ion battery

    CN107799822A

  • High-voltage electrolyte and lithium ion battery containing same

    CN111129588A

  • Electrolyte for inhibiting side reaction of battery positive electrode material and lithium ion battery

    CN114695958A